Memahami Hakikat Kehidupan Sosial Keagamaan Sebagai Solusi Alternatif Menghindari Konflik - Fuadi Fuadi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
The substance of social life is a man ability to understand that life is to become other people in togetherness based on the universal value of religion by dialogic theology approach. Developing creative thought concept on social would reduce tension and subjective claim on truths. Developing a productive economic system will cover any social conflict from indigent and economically oppressed community.